(untitled) (Fiep Bulletin - online, 2013)
Sex is a synonym of health, not only physical but also emotional. A good physical condition contributes to the pleasure in sexual activity, in addition to associate itself to improving self-esteem of the individual. This study is not just the sex as a form of human pleasure, but especially the relationship between the Practice of Regular Physical Activity Act and the Sexual and consequential physiological and psychological reactions occurred in the Human Body. The research is characterized as a field of study, a quantitative descriptive. We applied two questionnaires, one with 110 individuals who practice some form of regular physical activity and the other with 55 athletes from income. In general the majority of respondents agree that sex is health, improves self-esteem and that a good physical condition favors the sexual pleasure. However it was possible to see that talk of sex is still something delicate and often embarrassing.